2007
DOI: 10.1002/hep.21696
|View full text |Cite
|
Sign up to set email alerts
|

Preferential X chromosome loss but random inactivation characterize primary biliary cirrhosis

Abstract: Recent work has demonstrated enhanced X monosomy in women with primary biliary cirrhosis (PBC) as well as two other female-predominant autoimmune diseases, systemic sclerosis and autoimmune thyroid disease. To further our understanding of these events, we have investigated the mechanisms of X chromosome loss and X chromosome inactivation (XCI) in 166 women with PBC and 226 rigorously age-matched healthy and liver disease controls. X chromosome analysis and determination of loss pattern was performed by quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 34 publications
(47 reference statements)
1
86
1
Order By: Relevance
“…How these factors are molecularly involved in PBC onset remains unclear. Elsewhere, it was reported that X-chromosome gene expression instability might also participate in female predominance in the disease [64,65], and that monozygotic twins and sisters discordant for PBC exhibited particular epigenetic differences [66]. These collectively support the notion that epigenetic factors influence the onset of PBC.…”
Section: Epigenetics On Pbcmentioning
confidence: 65%
“…How these factors are molecularly involved in PBC onset remains unclear. Elsewhere, it was reported that X-chromosome gene expression instability might also participate in female predominance in the disease [64,65], and that monozygotic twins and sisters discordant for PBC exhibited particular epigenetic differences [66]. These collectively support the notion that epigenetic factors influence the onset of PBC.…”
Section: Epigenetics On Pbcmentioning
confidence: 65%
“…Interestingly, they found PBC patients to have an increased frequency of X chromosome monosomy in peripheral blood cells overall, as well as in all tested white blood cell subpopulations, suggesting an instabilty of the X chromosome related to PBC (91). Further work by this same group using quantitative flourescent PCR found the pattern of X chromosome loss to be preferential in PBC, compared to healthy and hepatitis C virus infected controls (92). In this same study, X chromosome inactivation (XCI) was also assessed, and no significant association between PBC and degree of XCI skewing was identified (92).…”
Section: The Sex Chromosomes and Pbcmentioning
confidence: 95%
“…Further work by this same group using quantitative flourescent PCR found the pattern of X chromosome loss to be preferential in PBC, compared to healthy and hepatitis C virus infected controls (92). In this same study, X chromosome inactivation (XCI) was also assessed, and no significant association between PBC and degree of XCI skewing was identified (92). Taken together, these findings suggest that particular X-linked alleles or haplotypes, likely in genes escaping XCI, might predispose to the development of autoimmunity as the result of haploinsufficiency due to the acquired monosomy, providing us with novel candidate regions for which to search and address in PBC.…”
Section: The Sex Chromosomes and Pbcmentioning
confidence: 96%
“…Importantly, this was observed in diseases with different organ specificities, including PBC, 19 scleroderma and autoimmune thyroid disease. 20 Loss of an X chromosome is indeed preferential and more frequently involves a parentally inherited one, 21 suggesting a possible critical involvement of X-chromosome gene product defects in the female preponderance of PBC and other autoimmune diseases, although new factors, such as microRNAs 22 or epigenetics, 23,24 should not be overlooked. Other authors have suggested that women affected with specific female-preponderant autoimmune diseases, i.e., scleroderma, manifest a skewed XCI pattern in their peripheral white blood cells.…”
Section: Introductionmentioning
confidence: 99%